Implementasi Latihan Genggam Bola Karet Pada Asuhan Keperawatan Pasien Stroke Dengan Gangguan Mobilitas Fisik Pada Ny. R Untuk Meningkatkan Kekuatan Massa Otot Di Wilayah Kerja Puskesmas Medan Sunggal - Annur Nilam Sari; Lily Putry Marito (STIKES Columbia Asia Medan, 2025)
Stroke is a major neurological disease that occurs in adults and the elderly, based on the high number of emergencies and the main cause of disability and death. The most common disorder in stroke is weakness or deficits in the musculoskeletal system such as parese or plegia. These conditions will cause various disorders in patients such as decreased muscle tone and strength, muscle weakness which if not treated immediately will lead to contractures, which ultimately cause impaired mobilization. Impaired fulfillment of daily activities and disability. Nursing actions to overcome physical mobility disorders are muscle strengthening exercises, especially in the upper extremities by holding a rubber ball. Purpose: Help solve the problem of physical mobility disorders to increase muscle strength in stroke patients with rubber ball grasping exercises. Methods: By collecting data from interviews and observations using case studies and subjects in stroke patients with nursing problems. Results: After performing the exercise of grasping a rubber ball for 2 times in 7 days there is an increase in muscle strength with a muscle strength value of 1/5 to 3/5. Conclusion: The action of grasping rubber ball exercises can increase muscle strength to overcome physical mobility disorders in stroke patients